TINJAUAN TINGKAT KEPUASAAN KERJA KARYAWAN PADA KANTOR PT. KALTIM PRIMA COAL SANGATTA KABUPATEN KUTAI TIMUR - Zumar, Muhammad (PREDIKSI, 2016)
Muhammad Zumar, Review the level of job satisfaction of employees in PT Kaltim Prima Coal Sangatta East Kutai district. This research aims to know how the level of job satisfaction of employees in PT Kaltim Prima Coal Sangatta East Kutai district. Overview of the level of job satisfaction of employees is measured with six indicators and eighteen sub or item indicator            Data questions are analyzed by using the average number so as it can be categorized the answers respondents by 50 people from the population of 150 people. Based on the value of the average indicator six or eighteen sub indicators/ items questions to measure varibael level overview of Employee Satisfaction obtained the value of the average employees job satisfaction variable of 3.46, this explains that employees satisfaction Level Overview PT Kaltim Prima Coal Sangatta East Kutai district is satisfactory, it means that the hypothesis are received.